The overview and role of heat shock proteins (HSP) especially HSP 60 and 70 in reproduction and other pathologies (a literature review) - Berestoviy , V.O.; Mahmood, Ahmad; Venckivska, I.B.; Ginzburg, V.G.; Sokol , I.V.; Berestoviy, O.O.; Govsieiev, D.O. (Medicni Perspektivi, 2021)
A search of peer-reviewed articles regarding heat shock proteins (HSP’s) especially HSP 60 and 70 was conducted in this review to understand its role in the development of various complications like miscarriage, preterm birth, tubal infertility and spontaneous abortion associated with chlamydial HSP 60 in IVF, male infertility, preeclampsia, cancer, immune system activation, autoimmune diseases, coronary heart disease, dysregulation of steroidal hormone from the endometrium and its up-regulation in stress response. ELISA, western blotting, immunofluorescence, and affinity chromatography were the most common methods researchers used to determine and separate HSP 60 and antibodies related to it. Heat shock proteins are responsible for normal folding of other proteins and prevent its abnormal folding and cause degradation of abnormally folded proteins, mitochondrial protein transport, DNA metabolism, regulation of apoptosis are their significant functions. HSP 60 is a homologue of bacterial HSP 60 (GroEL) and needs co-chaperonin HSP 10 for its proper functioning. Gynaecological and obstetrical complications were more prevalent in most studies. Pregnant women were mostly affected subjects. Abnormal HSP 60 leads to a high level of unfolded or misfolded proteins, which in turn activate other body systems to produce the clinical outcome. Some researchers stated that there is no association between preterm birth and HSP 60 & 70, chlamydial HSP 60 antibodies trigger tubal infertility, preeclamptic pregnancies has detectable HSP60 as compared to control, GroEL leads to tubal infertility and IVF failure, chlamydial (CHSP 60) activates autoimmunity. HSP60 seropositivity reduces the opportunities of ectopic pregnancy, levels of HSP 60 does not stay constant throughout the menstrual cycle in reference to control, while other opposed these conclusions in their research works. According to some researchers, HSP 60 is a risk factor for pregnancy-related pathologies development, and some other opposed this theory and considered HSP 60 as a safety factor for normal pregnancy outcome, according to this review harmful effect of HSP 60 dominate, in future further high-quality studies need to be done for better understanding.